Interrelations Between Virtual-World and Real-World Activities: Comparison of Genders, Age Groups, and Pathological and Nonpathological Internet Users - Bayraktar, Fatih; Amca, Hasan (Mary Ann Liebert, Inc, 2012)
After the Internet Revolution, people have started to spend most of their everyday time online carrying out virtual activities. A limited number of studies tried to answer whether virtual activities match our real-world (RW) activities. Moreover, to our knowledge, there was no study that dealt with these interrelations between virtual and RW activities among the pathological and nonpathological users of the Internet (i.e. PIUs and NPIUs). The primary aim of this study was to fill this gap and to investigate the correlations between virtual-world (VW) and RW activities among PIUs and NPIUs. The secondary aim was to examine the perceptions of the Internet and motivations to go online for PIUs and NPIUs. The third aim was to compare virtual and RW activities across gender and age groups. The results indicated that correlations between most of the activities in RW and VW were high among men and women, among age groups, and also among PIUs and NPUs. However, beyond these similarities, perceptions of the Internet and motivations to browse into VW were differed among PIUs and NPIUs. In other words, PIUs, but not NPIUs, perceived VW activities more gratified and had motivations to go online for gratified functions.
Keywords: Addiction; Online; Usage; Communication; Gratification; Adolescents; Motivations; Seeking